Vitamin E and immunity after the Kona Triathlon World Championship - Nieman, D. C.; Henson, D. A.; McAnulty, S. R.; McAnulty, L. S.; Morrow, J. D.; Ahmed, A.; Heward, C. B. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: To measure the influence of vitamin E ingestion on oxidative stress and immune changes in response to the Triathlon World Championship in Kona, Hawaii. METHODS: Thirty-eight triathletes received vitamin E (VitE) (800 IU x d(-1) alpha-tocopherol) or placebo (Pla) capsules in randomized, double-blind fashion for 2 months before the race event. Blood, urine, and saliva samples were collected the day before the race, 5-10 min postrace, and 1.5 h postrace. RESULTS: Race times did not differ between VitE (N = 19, 721 +/- 24 min) and Pla groups (N = 17, 719 +/- 27 min, P = 0.959), and both groups maintained an intensity of approximately 80% maximum heart rate during the bike and run portions. Plasma alpha-tocopherol was approximately 75% higher in the VitE versus Pla group prerace (24.1 +/- 1.1 and 13.8 +/- 1.1 micromol x L(-1), P < 0.001, respectively) and postrace. Plasma F2-isoprostanes increased 181% versus 97% postrace in the VitE versus Pla groups (P = 0.044). IL-6 was 89% higher (166 +/- 28 and 88 +/- 13 pg x mL(-1), respectively, P = 0.016), IL-1ra was 107% higher (4848 +/- 1203 and 2341 +/- 790 pg x mL(-1), respectively, P = 0.057), and IL-8 was 41% higher postrace in the VitE versus Pla groups (26.0 +/- 3.6 and 18.4 +/- 2.4 pg x mL(-1), respectively, P = 0.094). CONCLUSION: These data indicate that vitamin E (800 IU x d(-1) for 2 months) compared with placebo ingestion before a competitive triathlon race event promotes lipid peroxidation and inflammation during exercise.